Synthesis of Silver Nanoparticles using Gandaria Seeds Bioreductor - Bijang, Catherina M.; Hasanela, Nurani; Joris, Shielda N.; Fransina, Eirene G.; Tahril, Tahril; Azis, Thamrin; Tehuayo, Ahmadin (Jurnal Akademika Kimia, 2023)
The silver nanoparticles (NPP) are synthesized with the chemical reduction method by using a water extract bioreductor of gandaria seed (Bouea macrophylla G.) which acts as a reducing precursor, in this case, AgNO3 Ag+ is reduced to AgO. The concentration of AgNO3 is made between 0.5 mm and 1 mm. The characteristic of NPP is unstable, so a modification is needed with and without the addition of PVA 1 %. The process of NPP shaping is monitored by observing the uptaken of UV - Vis when the color changes occur. The high NPP concentration of AgNO3 has higher absorbance and is wider if compared to the lower AgNO3 concentration. The result of this research based on the absorbance value and the wavelength showed the NPP synthesized without the addition of PVA 1 % (b/v) is wider. The addition of PVA 1 % (b/v) provides better stability and maintains the absorbance of spectrum changes from day to day. The maximum uptaken of UV-Vis from NPP AgNO3 0.5 mm by using green synthesis and 1 mm without adding PVA are 0.946 and 0.980, respectively. However, NPP with the addition of PVA has 0.968 and 0.978 absorbance. The best concentration of NPP produced was 1 mm AgNO3.